IMPLEMENTASI DAN PERANCANGAN FAILOVER MENGGUNAKAN MODEL POOL PADA LAYANAN SMS BROADCAST - Wicaksono, Ryan; Ibnugraha, Prajna Deshanta; Hamdani, Budhi (TEKTRIKA, 2024)
The need to use multiple modems or what could be called multimodems is growing. Pool modems have the same working system as individual modems, only in the modem pool there are several modems placed in one box with the same power source. The modem pool can be configured to be able to broadcast SMS, because it has 8 ports, failover services can be used to broadcast SMS. Failover itself is a service where when one piece of hardware cannot perform its proper function, it will be transferred to the next piece of hardware so that the system continues to run as it should. The results of the design and implementation of failover to broadcast SMS to 30 numbers obtained a delay time of 5979 seconds, so that the average value of SMS sending was 199.3 seconds/SMS.